Edupreneurship in Early Childhood Education: Teachers' Perceptions of Entrepreneurship in the Digital Era - Yulianti, Enny; Reksadini, Marda Ulya; Andriyanto, Irsad; Khafidoh, Inayatul (Jurusan PIAUD UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to analyze early childhood education (ECE) teachers' perceptions of entrepreneurship in fostering edupreneurship in the digital era. The research is motivated by the fact that advancements in digital technology have transformed various aspects of life, including education. As such, entrepreneurship education has become crucial in preparing children for future challenges. ECE teachers, who play a pivotal role in the early stages of child development, are instrumental in instilling entrepreneurial values relevant to the evolving digital landscape. Data were collected through a questionnaire that included statements based on essential entrepreneurial skills. The survey, which involved 50 respondents, found that the majority of ECE teachers hold a positive view of the importance of entrepreneurial skills in preparing children for challenges in the digital age. Specifically, 19% strongly agreed, 54% agreed, 18% disagreed, 6% strongly disagreed, and 2% strongly disagreed with the statement on the significance of entrepreneurship in the context of edupreneurship. The findings highlight creativity, innovation, independence, and risk-taking as critical skills for entrepreneurs, particularly in the digital era. The ability to approach challenges from various perspectives is also crucial for identifying new opportunities in a digital world. This study underscores the importance of integrating entrepreneurship into early childhood education to equip children with essential skills for success in an increasingly digital environment. The contribution of this research lies in providing valuable insights into the role of entrepreneurship education at the ECE level as a foundation for nurturing children who are prepared for the digital world and for advancing the development of edupreneurship in the future.